The relationship among family business, corporate governance, and firm performance: An empirical assessment in the tourism sector - Rossella Leopizzi; Simone Pizzi; Fabrizio D'Addario (Administrative Sciences, 2021)
Tourism has been the subject of great attention of policy makers. The centrality of the sector derives from multiple factors, including the high number of subjects employed within the supply chain, the contribution to developing nations' economic growth, and the environmental implications of establishing new productive activities. Under this scenario, family holdings play a central role as the main types of organisations active in the sector. In this sense, an understanding of these companies' financial performance cannot disregard the understanding of the governance mechanisms that characterize the same given the potential divergence between 'family' and 'business' objectives. The research aims to encourage the development of new empirical evidence about this business model, providing specific contributions regarding the role of family members in companies' decision-making mechanisms. For our purposes, an empirical analysis based on the evaluation of 343 Italian hotels was built.
Keywords: 350; family business; agency theory; corporate governance; financial performance